Importance of Social Workers in Multidisciplinary Frontline Environment During Pandemics - Ahmed, Dunya (Issues in Social Science, 2024)
This pandemic was exaptational for lots of professions; however, the focus was mainly on medical staff front-liners. In this paper, we explore the different role of the social workers in alleviating the human-factor of the COVID-19 patients and their families The methodology of this study considers the multidisciplinary approaches that could enhance the social workers' role; since COVID-19 pandemic was not only a medical issue, but also a social issue. The study recommends a national governing body is set and to enforce standard practices as per the guidance of the social workers. The implication of the study shows the need for social workers in the new normal and the type of training and competency needed. A framework is proposed to prepare social workers pre-, during- and after-pandemics.